Attitudes of teachers towards inclusion of students with disabilities in physical education: Validity of the ATIPDPE-R instrument in Polish cultural context - Monika Cyran; Martin Kudláček; Martin Block; Iwona Malinowska-Lipień; Joanna Zyznawska (Palacký University Olomouc, 2017)
Background: Following the inclusion of children with disabilities in mainstream schools worldwide, legislative changes have recently been introduced in Poland, facilitating educational inclusion of individuals with disabilities. However, practical implementation still requires further action. Attitudes are a major determinant of teachers' behavior. Therefore, based on the Theory of Planned Behavior, the instrument Attitudes Toward Teaching Individuals with Physical Disabilities in Physical Education (ATIPDPE) has been developed, and adapted to cultural contexts in several countries (e.g. South Africa, Slovenia, and Greece). Objectives: The aim of this study was to estimate construct validity of the revised ATIPDPE-R instrument to the Polish cultural context (ATIPDPE-R-PL), in order to prepare a reliable scale to measure the attitudes of physical education (PE) teachers towards teaching students with physical disabilities in general PE classes.Methods: Participants were 158 in-service PE teachers (100 women and 58 men, range of age from 25 to 60, from primary and secondary schools) from Polish schools. Construct validity was obtained throughout the principal component analysis method (PCA). Reliability was estimated through Cronbach's alpha coefficient, where the value of at least .7 was accepted as satisfactory.Results: Based on the analysis, the attitudinal scale of ATIPDPE-R-PL measured three psychological components, which came from the PCA, and explained 66% of the variance similar to the original scale.Conclusions: The three components were positive and negative outcomes for students and negative outcomes for teachers, however items in each component varied from the original scale.